Beyond the role of participant: a firsthand account of the experiences of a patient-oriented research team - Lindsey Boechler (BMC, 2021)
Plain English Summary Immigrants often find accessing and navigating the healthcare system difficult upon arriving in Canada. Difficulties are often due to cultural differences, language barriers, limited health literacy, and health system complexity. This article shares the experiences of our research team as we engaged in patient-oriented research (POR) to better understand the unique barriers faced by newcomers trying to access and navigate the health system after immigrating to Canada. POR teams include researchers, patient partners, health care providers, and policymakers working together throughout each stage of the research process. This method of research embraces patient experience as expertise and provides patients an opportunity to influence decisions about their care. This research approach is aimed to improve patient outcomes by focusing on patient priorities. Through sharing our experiences, this article defines POR, describes the creation of our research team, and shares how impactful co-creating research with patients was for our team. Lastly, we provide examples of how taking a POR approach can increase research capacity and personal growth for both patient partners and researchers.